Forestry and reindeer husbandry in Sweden - Widmark, Camilla
Both the forestry sector and reindeer herders in Sweden use the forest resources, albeit for different purposes, and have adverse effects on each other. To reduce conflicts between them negotiations take place in so-called â€œconsultationsâ€ , but the institutional arrangement does not seem to be working well; the conflicts have not been resolved, and the reindeer herders are generally more dissatisfied with the outcome than the forest companies. This paper provides an overview of the parallel development of forestry and reindeer herding in the region. In addition several issues that complicate the consultations and need to be resolved in order to secure the continued co-existence of the two activities are identified, based on an analysis of physical, societal and judicial aspects of the relationship between them.